2003
DOI: 10.3354/meps251233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food consumption and temperature on growth rate and biochemical-based indicators of growth in early juvenile Atlantic cod Gadus morhua and haddock Melanogrammus aeglefinus

Abstract: ABSTRACT:The relationship between the somatic growth rate (G) and feeding level (unfed, intermediate, and maximum rations) of age-0 juvenile cod Gadus morhua and haddock Melanogrammus aeglefinus was quantified at different temperatures. Laboratory trials were conducted using 2 sizeclasses of cod (3.6 to 5.6 cm standard length [SL], and 8.1 to 12.4 cm SL) at 5, 8, 12, and 15°C, and 1 size-class of haddock (6.0 to 9.6 cm SL) at 8 and 12°C. The shape of the growth-feeding relationship was well described by a 3-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 28 publications
11
82
2
1
Order By: Relevance
“…The lack of a temperature effect on growth may be surprising given that many studies have found such an effect for cod, with increased temperature leading to increased growth (Jørgensen 1992, Shelton et al 1999, Dutil & Brander 2003, Peck et al 2003, Swain et al 2003. However, other studies have found that the impact of temperature may not be so straightforward and can differ depending on the thermal history experienced by the fish (Dutil et al 1999, Rindorf et al 2008.…”
Section: Discussionmentioning
confidence: 74%
“…The lack of a temperature effect on growth may be surprising given that many studies have found such an effect for cod, with increased temperature leading to increased growth (Jørgensen 1992, Shelton et al 1999, Dutil & Brander 2003, Peck et al 2003, Swain et al 2003. However, other studies have found that the impact of temperature may not be so straightforward and can differ depending on the thermal history experienced by the fish (Dutil et al 1999, Rindorf et al 2008.…”
Section: Discussionmentioning
confidence: 74%
“…The ecophysiological ENM incorporated a spawning temperature threshold of 0-9 • C between February and June. This is different from the temperature range that we have used for haddock (i.e., an with glacier template at 21 ka before present indicated by hatching (Peltier, 1994). The LGM bathymetry (sea level and 200 m depth) is derived from the 1 • sea level data of Peltier (1994) at 21 ka before present, interpolated to the 5 fields of ETOPO-5.…”
Section: Discussionmentioning
confidence: 99%
“…For haddock, the ICES-Fishmap (Haddock, 2009) gives a minimum temperature threshold of 6.5 • C, and Brodziak (2005) reports the juvenile and adult fish have been caught during fisheries surveys between temperatures of 2-16 • C. Peck et al (2003) give the temperature of maximum growth at 12 • C, which is approximately at the center of the summer climatological envelope of 6-18 • C that has been used to define its range in Fig. 1.…”
Section: Methods: An Ecological Niche Model (Enm) Based On Temperaturmentioning
confidence: 99%
“…This assumption is based on the relation between growth and condition, previously described by a multispecies model relating growth rate and sRD with respect to temperature in well-nourished larvae . Clearly, growth not only depends upon temperature, but also on the input of energy and nutrients (e.g., Peck et al, 2003) and most research seeks to deal with wellfeeding and growing organisms (i.e., when rates of anabolism exceed catabolism). Negative and positive growth rates are always examined in concert, implying a basic assumption that there are no major physiological differences in growing or mildly fasting animals, even though this is usually not explicitly stated.…”
Section: Body Size and Life Stage Effect On Starvation Ratementioning
confidence: 99%